Food, water and wine in the medicinal practices of Oribasius (4th century CE) - Carvalho, Margarida Maria de (Romanitas - Revista de Estudos Grecolatinos, 2025)
Oribasius of Pergamum was a Neoplatonic doctor from Late Antiquity, more specifically from the period of approximately 320 to 403. His work was considered for a long time to be a mere compilation of Galen. We reject this idea when we see that there are several medical supplements updated by this doctor in his time. In this article, we aim to analyze food, water, and wine in the medicinal practices of Oribasius. In terms of food, we chose to talk about red meat. All these elements are part of the medical diet written by Oribasius for Emperor Julian and his military troops.
Keywords: Oribasius; Food; Water